Acute Epstein-Barr infection presenting as cholecystitis with ascites. Issue 1 (8th January 2020) - Teopoulos Lamprianidis, Konstantinos; Easom, Nicholas; Patch, Emma; Thomas, Sherine
Abstract : A young female patient presented with features of ascites and cholecystitis. She was subsequently diagnosed with an acute Epstein-Barr virus infection. This is a rare presentation of a common infection. The patient was managed conservatively and the illness resolved within 6 weeks.